2003
DOI: 10.1191/0748233703th184oa
|View full text |Cite
|
Sign up to set email alerts
|

5-HT loss in rat brain by type II pyrethroid insecticides

Abstract: A serotonin depleting effect was produced by these type II pyrethroids. The concentration of 5-HT and its metabolite 5-HIAA decreased in the brain regions from pyrethroid treated animals. Pyrethroids accelerated the turnover of 5-HT in midbrain and striatum areas. It is concluded that pyrethroids affect serotonin neurotransmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 44 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Moreover, other effects have been involved such as effects on voltage sensitive calcium channels, voltage sensitive chloride channels, GABA A receptors and on the release of neurotransmitters (Narahashi, 1996;Martínez-Larrañaga et al, 2003;Hossain et al, 2004;Shafer et al, 2005;Ray and Fry, 2006;Brown et al, 2006;Nasuti et al, 2007;Breckenridge et al, 2009). In the present study, we showed that the pyrethroid cyfluthrin produced in a dose-dependent manner a statistically significant decrease of the 5-HT levels in all brain regions studied (hypothalamus, striatum, midbrain, hippocampus and prefrontal cortex).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, other effects have been involved such as effects on voltage sensitive calcium channels, voltage sensitive chloride channels, GABA A receptors and on the release of neurotransmitters (Narahashi, 1996;Martínez-Larrañaga et al, 2003;Hossain et al, 2004;Shafer et al, 2005;Ray and Fry, 2006;Brown et al, 2006;Nasuti et al, 2007;Breckenridge et al, 2009). In the present study, we showed that the pyrethroid cyfluthrin produced in a dose-dependent manner a statistically significant decrease of the 5-HT levels in all brain regions studied (hypothalamus, striatum, midbrain, hippocampus and prefrontal cortex).…”
Section: Discussionmentioning
confidence: 98%
“…Following sample collections, 300-800 ml of 0.4 M HClO 4 containing 0.1% (w/v) Na 2 S 2 O 5 was added to the tissues, and the mixture was homogenized (1 min) by sonication (Labsonic U-Braun) before neurochemical evaluation was performed. The homogenates were centrifuged (RC5C, Sorvall Instruments) at 12,000g for 20 min at 4 ºC and aliquots of supernatants were taken for analysis of dopamine (DA) and its metabolites [3,4-hydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA)] and serotonin (5-HT) and its metabolite [5-hydroxy-3-indolacetic acid (5-HIAA)] using a high performance liquid chromatography (HPLC) technique with electrochemical detection (Colado et al, 1993) with modifications (Martínez-Larrañaga et al, 2003).…”
Section: Determination Of Monoamine Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term effects of pyrethroid exposure are not clear. The most commonly examined effects in epidemiological and animal studies include neurotoxicity, neurobehavioral and neurodevelopment effects as well as endocrine disrupting effects (Martínez-Larrañaga et al, 2003;Shafer et al, 2005;Mckinlay et al, 2008;Wolansky and Harrill, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DM caused neuronal apoptosis, accompanied by increased expression of proapoptotic p53 and Bax, and decreased expression of antiapoptotic Bcl-2 (Wu et al, 2000;Wu and Liu, 2000a, b). Deltamethrin also selectively increased dopamine release and uptake in the dopaminergic nerve terminals of the striatum, and even altered serotonergic neurotransmission (Kirby et al, 1999;Martinez-Larrañaga et al, 2003). Environmental or occupational exposure to pyrethroid pesticides, therefore, may produce specific damage to dopaminergic neurons, but the full extent of DM-induced neuropathology is still unknown.…”
Section: Introductionmentioning
confidence: 99%